PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN DAN KOMITMEN TERHADAP KINERJA KARYAWAN JASA KONSULTANSI - Arie Putu Ardhika (Universitas Pendidikan Nasional, 2013)
Labor or employee is a factor of production that is constantly moving and alwayschanging, has sense and feelings and motivations, if labor as a factor of production had thepleasure to work with passion and excitement, it is certain that the goals set by the companyor organization will be more easily achieved. Performance of employees perceived greaterrole in organizational life, whether in government or in private companies, this is because theposition of an employee is the determining factor in the success of the planned activitieswhich constitute the goals and objectives to be achieved by an organization. In a ConsultancyServices firm whose judgment judged by the quality of the work force expert, certainly has adifferent level of employee performance due to differences in level of education, commitment,and experience of a person that directly affect the level of employee performance. Therefore.companies need to look for efforts to improve employee performance, to get a ConsultancyServices firm that is ready to compete. Before determining the measures to be taken by thecompany's good to know how big or how significant these three variables affect theperformance of the employees.The approach used in this research is exploratory and descriptive analyticalapproach. Data collected through questionnaires and in-depth interviews with respondents.Data analysis was performed by descriptive qualitative Likert scale used to measure theattitudes, opinions and perceptions of employees CV. Amertha Nirwana.The results showed that the effect of the level of education, experience and commitment toemployee performance CV. Amertha Nirvana is as high as 79.6% with the regressionequation Y = -1.456 + 0.149 X1 + 0.209 X2 + 0.146 X3 which means that experience thegreatest impact, followed by education level and the lowest influence was committed whilethe remaining 20.4% are influenced by factors other.Keywords: employee performance, level of education, experience and commitment.